Pramipexole Impairs Stimulus-Response Learning in Healthy Young Adults - Gallant, Haley; Vo, Andrew; Seergobin, Ken N.; MacDonald, Penny A. (Frontiers in Neuroscience, 2016)
Dopaminergic therapy has paradoxical effects on cognition in Parkinson's disease (PD) patients, with some functions worsened and others improved. The dopamine overdose hypothesis is proposed as an explanation for these opposing effects of medication taking into account the varying levels of dopamine within different brain regions in PD. The detrimental effects of medication on cognition have been attributed to exogenous dopamine overdose in brain regions with spared dopamine levels in PD. It has been demonstrated that learning is most commonly worsened by dopaminergic medication. The current study aimed to investigate whether the medication-related learning impairment exhibited in PD patients is due to a main effect of medication by evaluating the dopamine overdose hypothesis in healthy young adults. Using a randomized, double-blind, placebo-controlled design, 40 healthy young undergraduate students completed a stimulus-response learning task. Half of the participants were treated with 0.5 mg of pramipexole, a dopamine agonist, whereas the other half were treated with a placebo. We found that stimulus-response learning was significantly impaired in participants on pramipexole relative to placebo controls. These findings are consistent with the dopamine overdose hypothesis and suggest that dopaminergic medication impairs learning independent of PD pathology. Our results have important clinical implications for conditions treated with pramipexole, particularly PD, restless leg syndrome, some forms of dystonia, and potentially depression.